METODE PENGEMBANGAN EMPATI ANAK USIA 5-6 TAHUN PADA KELUARGA DI TK BINA ANAK MUSLIM KOTA SINGKAWANG - Delvia Dwi Putri; Aunurrahman Aunurrahman; Marmawi R (Universitas Tanjungpura, 2021)
AbstractThis study aimed to describe the method of developing empathy for children aged 5-6 years in families at Bina Anak Muslim Kindergarten in Singkawang City. The research method used is descriptive method in the form of qualitative research. Subjects in this study were parents, totaling 10 people at Bina Anak Muslim Kindergarten in Singkawang City. The location of this research was at the parents' house, namely in Pasiran Village, West Singkawang District. This study used two data collection techniques were documentation and interviews. The results of this study showed that the storytelling method was carried out by parents by providing material according to the child's condition through story books and videos displayed via cellphones, the lecture method was carried out by parents through an approach to children accompanied by advice and examples of actions taken by parents so that children would imitate what parents say, while the habituation method is applied through daily activities accompanied by an approach with children, giving children the opportunity to do something related to empathy towards friends and the surrounding environment and getting children to share.Keywords: Development Method Empathy